A dynamic evaluation of how kick point location influences swing parameters and related launch conditions - Joyce, C.; Burnett, A.; Reyes, A.; Herbert, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
In golf, many parameters of the driver can be modified to maximise hitting distance. The main objective of this study was to determine whether drivers fitted with shafts having high and low kick points would alter selected swing parameters and related launch conditions. In total, 12 elite male golfers (handicap score = 1.2 ± 1.8) had three shots analysed for two drivers fitted with `stiff` shafts with differing kick point location. Stiffness profiles of these shafts were also measured. Five swing and related launch parameters were measured using a real-time launch monitor. The locations of the low and high kick points on each shaft during the golf swing (the dynamic kick points) were confirmed via motion analysis. The driver fitted with the shaft containing the high kick point displayed a more negative (steeper) angle of attack (p < 0.01), a lower launch angle (p < 0.01) and an increased spin rate (p < 0.01) when compared to a driver fitted with a low kick point shaft. It is possible that the attack angle differed between drivers due to the greater amount of shaft bending found late in the downswing (80% of the downswing and just before impact). Future work is needed in this under-researched area to determine why these differences occurred.